The Rāmāyaṇa revisited - Bose, Mandakranta, 1938- (Oxford University Press, 2004)
14 leading 'Ramayana' scholars examine the epic in its myriad contexts throughout South and Southeast Asia. They explore the role the narrative plays in societies as varied as India, Indonesia, Thailand and Cambodia. The essays also expand the understanding of the 'text' to include non-verbal renditions of the epic.